Two new empoascine leafhopper genera and species (Hemiptera: Cicadellidae: Typhlocybinae) from southern China, with a key to Chinese genera of Empoascini - Qin, Dao-Zheng; Zhang, Ya-Lin (Zootaxa, 2008)
Two new genera and species of empoascine leafhoppers, Luodianasca recurvata and Treufalka lamellata are described from southern China. A key to these and other Empoascini genera from China is also provided.